2016
DOI: 10.1097/icb.0000000000000223
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Effusion as an Ocular Manifestation of Immunoglobulin G4–related Disease

Abstract: Choroidal effusion may be an ocular manifestation of IgG4-related disease. Oral corticosteroids is an effective treatment. Ophthalmologists should be aware of this possible finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…In other reports describing patients presenting with IgG4related retinal and choroidal lesions subsequently underwent lumbar puncture and flow cytometry analysis. 1,3,4 Similarly, our case did not have evidence of vitritis, and lumbar puncture and flow cytometry were unremarkable, decreasing the likelihood of intraocular lymphoma. In cases of sarcoidosis, granulomatous inflammation would be expected and also observed on histopathology of other organs.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…In other reports describing patients presenting with IgG4related retinal and choroidal lesions subsequently underwent lumbar puncture and flow cytometry analysis. 1,3,4 Similarly, our case did not have evidence of vitritis, and lumbar puncture and flow cytometry were unremarkable, decreasing the likelihood of intraocular lymphoma. In cases of sarcoidosis, granulomatous inflammation would be expected and also observed on histopathology of other organs.…”
Section: Discussionsupporting
confidence: 56%
“…Interestingly, the sex ratio for IgG4-related autoimmune pancreatitis is 3:1 men to women, whereas head-and neck-related disease has roughly equal proportions between men and women. 1,3,4 A Japanese study evaluating IgG4-ROD in 65 patients found that the lacrimal gland was the most involved orbital structure (88%). Other IgG4related lesions were also found to involve the trigeminal nerve (39%), extraocular muscles (25%), Supported by the Macula Foundation Inc, New York, NY.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are six reported cases of IgG4-related choroidal mass 2-7 and one reported case of choroidal effusion. 8 Our case is the first case that demonstrates sequential but heterogeneous involvement of the fellow eye, which developed anterior uveitis while on high-dose steroids. With the prompt commencement of rituximab and second-line immunosuppressants, the condition of the fellow eye was brought under control with visual acuity preserved.…”
Section: Discussionmentioning
confidence: 70%